Development and application of bio-waste-derived adsorbents for the removal of boron from groundwater - Ayesha Y., Ahmad (2022)
This study investigates the development and application of bio-waste-derived adsorbents for the removal of boron from groundwater. The boron removal from groundwater was explored by bio-waste-derived adsorbents such as roasted date pits (RDPs) and modified roasted date pits (MDPs) by mercaptoacetic acid. The results were also compared with the commercially available adsorbents such as activated carbon and bentonite. Several experimental conditions, including pH, temperature, and initial concentration were investigated. Various analytical techniques were used to investigate surface characterizations, functional groups and morphological changes of the adsorbents via Fourier transform infrared spectroscopy (FTIR), Brunauer Emmett Teller (BET), and scanning electron microscopy (SEM). In addition, four adsorption models are utilized to analyze the adsorption process, including Langmuir, Dubinin-Radushkevich, Freundlich, and Temkin. The results showed that the modified roasted date pits (MDPs) could be used as an affordable, environmentally friendly, and effective adsorbent for boron removal from groundwater (GW). Negative Gibbs energy (ΔG°) values imply a spontaneous and favorable adsorption process, which is more favorable and spontaneous at high temperatures. The adsorption process was governed by positive entropy values (ΔS°), which suggests that the adsorbate–adsorbent complex may have undergone structural alterations or readjustments.